Clinical and economic analysis of the use of apixaban for the treatment of venous thromboembolic events - O. V. Shatalova (Рациональная фармакотерапия в кардиологии)
Aim. Pharmacoeconomic analysis of apixaban use compared to conventional therapy in patients with venous thromboembolism (VTE).Material and methods. Economic evaluation was performed from a position of the health care system. The cost analysis, "cost-effectiveness" analysis, "impact on the budget” analysis, and sensitivity analysis were fulfilled.Results. In real clinical practice in hospitals direct medical costs of apixaban treatment of deep vein thrombosis and pulmonary embolism make up 2331.67 and 3142.98 rubles, respectively, while the costs of the standard therapy - 6192.15 and 6225.75 rubles. Potential resource savings will reduce 2.65 times the cost of the health system. The share of the costs of treatment of adverse effects (bleeding) in the conventional therapy group was 4.8 times higher than the costs in apixaban group. The results of analysis of the effect on the budget show a decrease in the load on the budget when apixaban was included in the treatment regimen of VTE. Potential resource savings of the health system in the treatment of 1,000 patients with apixaban will account 3,911,860 rubles in comparison with conventional therapy.Conclusion. The inclusion of apixaban in the therapy of VTE can significantly reduce the burden on the budget of the health care system.